MEDIASI MOTIVASI KERJA PADA HUBUNGAN KOMPENSASI DENGAN KOMITMEN ORGANISASIONAL - I Gede Riana; Rai Mutiara Sari; I B Udayana Putra (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
Organizational commitment is the identification, loyalty, and involvement expressed by employees, organizations or organizational units. Organizational commitment is also seen as an affective response to the organization as a whole, which then shows an affective response to specific aspects of the work. This research is to find out the mediating role of work motivation on the effect of compensation on organizational commitment. This study uses a saturated sample technique with a population of 146 employees with a response rate of 73.79%, namely 107 employees. Furthermore the data collected has been analyzed using path analysis techniques. The results showed that four proposed hypotheses could be accepted. Compensation has positive and significant effect on organizational commitment, compensation has positive and significant effect on work motivation, and work motivation has a positive and significant effect on organizational commitment. However, this study also inform that work motivation significantly mediates the effect of compensation on organizational commitment.